2013
DOI: 10.1002/hlca.201200305
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Natural Atisane‐Type Diterpenoids by retro‐Biomimetic Transformations

Abstract: An efficient one step, retro-biomimetic procedure for the synthesis of natural products having the atisane structure is described (Scheme 2), natural products which are components of medicinal plants and possess relevant biological activity. Their structures were confirmed by chemical transformations and spectral data. The starting materials were the known ent-kaur-16-en-19-oic acid (1) and ent-trachyloban-19-oic acid (2), diterpenoids readily available from the waste of sunflower.Introduction. -Tetracyclic at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Since both ent-kaur-16-en-19-oic acid and ent-trachyloban-19-oic acid co-occur in the sunflower, Helianthus annuus, treatment of the waste from the production of sunflower oil with the super-acid, fluorosulfonic acid at −60 °C followed by triethylamine, gave a high yield of the corresponding ent-atisir-15-and -16-enes. 14 Diazotisation of ent-beyerene-16-amine with the exo-configuration gave ent-kauran-16ol and ent-kaurenes together with smaller amounts of the corresponding ent-beyeran-16-ols and beyerenes. 15 Thus it is possible to interconvert these skeleta and favour the formation of the ent-atisirenes.…”
Section: Reactions Of the Alkenes With Acidmentioning
confidence: 99%
“…Since both ent-kaur-16-en-19-oic acid and ent-trachyloban-19-oic acid co-occur in the sunflower, Helianthus annuus, treatment of the waste from the production of sunflower oil with the super-acid, fluorosulfonic acid at −60 °C followed by triethylamine, gave a high yield of the corresponding ent-atisir-15-and -16-enes. 14 Diazotisation of ent-beyerene-16-amine with the exo-configuration gave ent-kauran-16ol and ent-kaurenes together with smaller amounts of the corresponding ent-beyeran-16-ols and beyerenes. 15 Thus it is possible to interconvert these skeleta and favour the formation of the ent-atisirenes.…”
Section: Reactions Of the Alkenes With Acidmentioning
confidence: 99%
“…Structural drawings were produced using Ball & Stick [8]. The results of calculations on cations C -E with the attached COOH group present in the natural products from [3] indicated that the COOH group has little effect on the rearrangement chemistry and carbocation structures. …”
Section: Experimental Partmentioning
confidence: 99%
“…Despite extensive theoretical studies revealing energetically viable pathways to these diterpenes (Scheme) [2], the intermediacy of several unusual carbocations F -H (Fig. 1) has still been advocated for in the recent literature [3]. Herein, we expand on our previous work to specifically address the energetic viability of carbocations F -H 1 ).…”
mentioning
confidence: 95%
“…Recently [49] an effi cient one-step, retro-biomimetic procedure for the synthesis of natural products having the atisane structure has been reported (Scheme 10), which are natural components of medicinal plants and possess a relevant biological activity. As a part of the program of transformation the diterpenoids by microorganisms, Silva et al [51] carried out the transformation of ent-kaur-16-en-19-oic acid 1, by using Rhizopus stolonifer.…”
Section: Scheme 9 Photooxygenation Reactions Of Ent-kaurenoic Acid 1mentioning
confidence: 99%